Biasing human epidermal growth factor receptor 4 (HER4) tyrosine kinase signaling with antibodies: Induction of cell death by antibody‐dependent HER4 intracellular domain trafficking. Issue 7 (8th June 2020) - Lanotte, Romain; Garambois, Véronique; Gaborit, Nadège; Larbouret, Christel; Musnier, Astrid; Martineau, Pierre; Pèlegrin, André; Chardès, Thierry
Abstract: Human epidermal growth factor receptor 4 (HER4) isoforms have oncogenic or tumor suppressor functions depending on their susceptibility to proteolytic cleavage and HER4 intracellular domain (4ICD) translocation. Here, we report that the neuregulin 1 (NRG1) tumor suppressor mechanism through the HER4 JMa/CYT1 isoform can be mimicked by the agonist anti‐HER4 Ab C6. Neuregulin 1 induced cleavage of poly(ADP‐ribose) polymerase (PARP) and sub‐G1 DNA fragmentation, and also reduced the metabolic activity of HER3 − /HER4 + cervical (C‐33A) and ovarian (COV318) cancer cells. This effect was confirmed in HER4 JMa/CYT1‐, but not JMa/CYT2‐transfected BT549 triple‐negative breast cancer cells. Neuregulin 1 favored 4ICD cleavage and retention in mitochondria in JMa/CYT1‐transfected BT549 cells, leading to reactive oxygen species (ROS) production through mitochondrial depolarization. Similarly, the anti‐HER4 Ab C6, which binds to a conformational epitope located on a.a. 575‐592 and 605‐620 of HER4 domain IV, induced 4ICD cleavage and retention in mitochondria, and mimicked NRG1‐mediated effects on PARP cleavage, ROS production, and mitochondrial membrane depolarization in cancer cells. In vivo, C6 reduced growth of COV434 and HCC1187 tumor cell xenografts in nude mice. Biasing 4ICD trafficking to mitochondria with anti‐HER4 Abs to mimic NRG1 suppressor functions could be an alternative anticancer strategy. Abstract : Neuregulin 1 (NRG1) induced cleavage of poly(ADP‐ribose) polymerase (PARP) in human epidermal growth factor receptor 4 (HER4) JMa/CYT1‐expressing cancer cells. NRG1 favored HER4 intracellular domain (4ICD) cleavage and retention into mitochondria leading to reactive oxygen species (ROS) production through mitochondrial depolarization in HER4 JMa/CYT1‐expressing cancer cells. Phage‐displayed selected anti‐HER4 Ab C6 induced 4ICD cleavage and retention into mitochondria, mimicking NRG1‐mediated effects on PARP cleavage, ROS production, and mitochondrial membrane depolarization. C6 Ab reduced in vivo growth of ovarian COV434 and breast HCC1187 tumor cell xenografts in nude mice.